2015
DOI: 10.7181/acfs.2015.16.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Chronic Complicated Scalp and Dural Defects Using Acellular Human Dermis and Latissimus Dorsi Myocutaneous Free flap

Abstract: We present reconstruction of a complicated scalp-dura defect using acellular human dermis and latissimus dorsi myocutaneous free flap. A 62-year-old female had previously undergone decompressive craniectomy for intracranial hemorrhage. The cranial bone flap was cryopreserved and restored to the original location subsequently, but necessitated removal for a methicillin-resistant Staphylococcal infection. However, the infectious nidus remained in a dermal substitute that was left over the cerebrum. Upon re-explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
4
0
4
Order By: Relevance
“…Besides their orthotopic use, acellular skin grafts are frequently used as heterotopic grafts in various body sites 5 , 23 25 . In this study, we have shown that human AS is significantly more elastic compared to human ATMF and ADM.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their orthotopic use, acellular skin grafts are frequently used as heterotopic grafts in various body sites 5 , 23 25 . In this study, we have shown that human AS is significantly more elastic compared to human ATMF and ADM.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective case series suggest that hADMs are a reliable adjunct in the reconstruction of the neuro-and viscero-cranium, such as the correction of bone and dura madre full-thickness defects or the contour deformities of the scalp secondary to trauma. 12,35 Recently, a promising experience was also reported in the surgical treatment of the aplasia cutis congenital defect of the scalp dermo-hypodermic tissues. 36 and homologous skin grafts or paraffine gauze can be used as a coverage.…”
Section: Scalpmentioning
confidence: 99%
“…The hADMs sheets can be easily used in dura madre (ie, post‐craniotomy duraplasty) or skull base reconstruction: among the reported advantages, no cases of cerebrospinal or adherences formation and little or no morbidity in the endoscopic reconstruction of large anterior skull base defects (> 2 cm) using commercial hADM. Several retrospective case series suggest that hADMs are a reliable adjunct in the reconstruction of the neuro‐ and viscero‐cranium, such as the correction of bone and dura madre full‐thickness defects or the contour deformities of the scalp secondary to trauma 12,35 . Recently, a promising experience was also reported in the surgical treatment of the aplasia cutis congenital defect of the scalp dermo‐hypodermic tissues 36 …”
Section: Head and Neckmentioning
confidence: 99%
“…Therefore, dural substitutes made from allogeneic dura mater were gradually withdrawn from the historical stage when the source of the dura mater was insufficient and the transmission of prions could not be completely avoided [24,25]. Domestic and foreign scholars have also tried to use amniotic membrane, dermis, and other allogenic materials to prepare dural substitutes and have achieved some positive results [26][27][28]. However, owing to the lack of sources of allogenic materials, this type of material has not been widely used.…”
Section: Allogeneic Tissue Materialsmentioning
confidence: 99%